Complications of Bicruciate-Retaining Total Knee Arthroplasty: The Importance of Alignment and Balance - Perreault, Caroline; Al-Shakfa, Fidaa; Lavoie, Frédéric (The Journal of Knee Surgery, 2023)
Bicruciate-retaining total knee arthroplasty (BCR TKA) results in kinematics closer to the native knee and in greater patient satisfaction but information concerning its outcome and complications is lacking.The goal of this study is to report the clinical and radiological outcomes of BCR prosthesis implanted using a spacer-based gap balancing technique and to assess if some preoperative factors are associated with a worse prognosis.A cohort of 207 knees in 194 patients who underwent BCR TKA, with a minimum 1-year follow-up, was retrospectively analyzed.Patients were followed at 6 weeks, 6 months, 1 year, and then every following year postoperatively, and filled questionnaires (Knee Society and Knee injury and Osteoarthritis Outcome Score) at every visit. Clinical and radiological assessments included range of motion, knee alignment, pain, and complications as defined by the Knee Society's Standardized list and definition of Complication of Total Knee Arthroplasty.Forty-three knees (20.8%) suffered major complications. Twenty-one knees (10.1%) underwent revision at an average of 32.1 months after the index procedure. Revision-free survival at 100 months was 85.7%. Revision was performed for aseptic tibial loosening in eight knees (3.9%) and stiffness in five knees (2.4%). There were 29 reoperations other than revision (14.0%), the most frequent procedure being manipulation under anesthesia in 14 knees (6.8%). Minor complications included tendonitis (20.8%), persistent synovitis (6.8%), and superficial wound infections (6.3%).All outcomes scores were greatly improved at the 1-year follow-up compared with preoperatively (p < 0.001). However, maximum flexion at the last follow-up was significantly reduced compared with preoperatively (mean maximum flexion ± standard deviation: 119.9 ± 15.6 vs. 129.9 ± 14.4, p < 0.001). Aseptic tibial loosening was associated with a hypercorrection in varus of preoperative valgus knees (p = 0.012).BCR TKA can give functional results similar to other types of prostheses but involves a substantial risk of complications. Important factors that can explain failed BCR TKA and guide its use were identified, more particularly knee alignment and its role in aseptic tibial loosening.
Keywords: total knee arthroplasty; bicruciate-retaining; complications; alignment; revision